Korelacija fizičke aktivnosti sa stresom, depresivnošću i anksioznošću kod studentica - Pilipović-Spasojević, Olivera; Ponorac, Nenad; Spremo, Mira (Scripta Medica, 2020)
Background/Aim: The period of beginning of studies is a stressful period of life in which students are expected to develop skills and abilities with which they will be able to take on the most important roles in all areas of social activity. Physical activity (PA) triggers and remodels mental health. The aim of the study was to determine the correlation between PA and stress, anxiety and depression in female students. Methods: Epidemiological observational study was performed and included a representative sample of 408 healthy female students aged 19 to 22 years. Questionnaires were used and anthropometric measurement of weight and body mass index (BMI) calculation was performed. Used questionnaires were: a socio-demographic questionnaire, standardised tests: DASS-21 test (short version) for mental health assessment and International Physical Activity Questionnaire - IPAQ test (long version). Results: Mean age of female students was 20.5 ± 0.72 years, average height 168.65 ± 6.01 cm, body weight 63.09 ± 9.9 kg, and BMI 22.1 ± 3.2. A significant negative correlation was found between high PA and anxiety (r = -0.160, p = 0.001), PA and depression (r = -0.118, p = 0.01), while the category of stress had a low correlation with PA. Conclusion: This research shows that a high level of PA has no effect on stress but has an effect on reducing anxiety and depression. Carefully planned physical activities can affect the emotional status of young female students.
Keywords: Fizičko zdravlje; Mentalno zdravlje; Ženski studenti; Anksioznost; Depresija